Examining the Depiction of Patriarchal Culture in Disney Mulan Movie 2020 - Yasmin Faisa Shofian; Yeny Prastiwi (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to analyze the patriarchal culture reflected in the film Mulan (2020), focusing on how patriarchal power structures and gender norms affect the journey of the main character, Mulan. The main issue raised is gender inequality that appears in the film's narrative, where Mulan struggles to fight social restrictions that place women in traditional roles as wives and mothers. The method used is a qualitative approach with content analysis of the script and visual elements of the film to identify the representation of patriarchy in the story, characters, and symbolism. The results of the study show that the film depicts patriarchy through social expectations of women and Mulan's resistance to these gender roles, which ultimately conveys a message about gender equality and women's empowerment in fighting patriarchal norms.